Saint Paul and philosophy: the consonance of ancient and modern thought - Cimino, Antonio; Heiden, Gerrit Jan van der; Kooten, George Henry van (De Gruyter eBook-Paket Philosophie, 2017)
The much-acclaimed present-day philosophical turn to the letters of Saint Paul points to a profound consonance between ancient and modern thought. Such is the bold claim of this study in which scholars from contemporary continental philosophy, new testamentary studies and ancient philosophy discuss with each other the meaning Paul's terms pistis, faith. In this volume, this theme discusses in detail the threefold relation between Paul and (1) continental thought, (2) the Graeco-Roman world, and (3) political theology. It is shown that pistis does not only concern a mode of knowing, but rather concerns the human ethos or mode of existence as a whole. Moreover, it is shown that the present-day political theological interest in Paul can be seen as an attempt to recuperate Paul’s pistis in this comprehensive sense. Finally, an important discussion concerning the specific ontological implications and background of this reinterpretation of pistis is examined by comparing the ancient ontological commitments to those of the present-day philosophers. Thus, the volume offers an insight in a crucial consonance of ancient and modern thought concerning the question of pistis in Paul while not forgetting to stipulate important differences.